Constructing Indian Christianities : culture, conversion, and caste - Bauman, Chad M,Ed; Young, Richard Fox,Ed (Routledge, 2019)
This volume offers insights into the current ‘public-square’ debates on Indian Christianity. Drawing on ethnographic fieldwork as well as rigorous analyses, it discusses the myriad histories of Christianity in India, its everyday practice and contestations and the process of its indigenisation. It addresses complex and pertinent themes such as Dalit Indian Christianity, diasporic nationalism and conversion. The work will interest scholars and researchers of religious studies, Dalit and subaltern studies, modern Indian history, and politics.